s-Conditionally Permutable Subgroups and p-Nilpotency of Finite Groups - Li, X. H.; Xu, Y. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the p-nilpotency of a group such that every maximal subgroup of its Sylow p-subgroups is s-conditionally permutable for some prime p. By using the classification of finite simple groups, we get interesting new results and generalize some earlier results.